Minimax-robust filtering of functionals from periodically correlated random fields - Iryna Golichenko (Cogent Mathematics, 2015)
The problem of optimal estimation of linear functionals depending on unknown values of periodically correlated random field from observations of the field with noise is considered. Formulas for calculating mean square errors and spectral characteristics of optimal linear estimates of the functionals are derived in the case where spectral densities are exactly known. Formulas that determine least favourable spectral densities and minimax (robust) spectral characteristics are proposed in the case where spectral densities are not exactly known but a class of admissible spectral densities is given.